Atlantoaxial Subluxation in an Adult Bitch - Diagnostic and Treatment by Ventral Surgical Stabilization - Cabreira, Adan; Dias da Silva, Murilo Henrique; Bregalioli, Thales; Covino Diamante, Gabriel Antonio (Acta Scientiae Veterinariae, 2024)
Background: Atlantoaxial subluxation can be a complex syndrome in dogs and is an important cause of morbidity and even mortality among small dogs specially toy breeds, but it can also happen in large breed dogs and cats. Those patients are predisposed to congenital malformations of the craniocervical and cervical joints. The atlantoaxial subluxation condition presents neurological alterations due to joint instability, vertebral misalignment, and subsequent compression and injury to the spinal cord parenchyma. The present study aims to report a case of atlantoaxial instability in a bitch Yorkshire Terrier, through surgical treatment using a modified ventral (parasagittal) approach. Case: A 7-year-old spayed bitch Yorkshire Terrier, weighing 4.5 kg, was brought to Ortho Support Pet with a complaint of vocalization suggestive of pain when jumping off the sofa. During the clinical/neurological examination, the animal exhibited signs consistent with a cervical syndrome. The diagnosis was made through a computed tomography scan, which revealed dorsal displacement of the axis in relation to the atlas. As a result, surgical treatment was initiated using the modified ventral stabilization technique (parasagittal) with screws and polymethylmethacrylate. However, the patient experienced a recurrence of the neurological symptoms 7 days after the surgical procedure, attributed to implant failure. A 2 nd surgical intervention was performed to provide a more rigid construction, resulting in therapeutic success. Discussion: The patient exhibited non-ambulatory tetraparesis after jumping off the sofa. The animal’s caregiver reported that similar episodes had occurred in the past during the pet’s life. It’s worth noting that although most animals display clinical signs before the age of 6 months, older patients can also develop atlantoaxial subluxation due to joint instability, as described in this case report. Animals affected by atlantoaxial subluxation can manifest a range of symptoms, from cervical pain to tetraplegia, and, in severe cases, even respiratory failure leading to death. The presentation of signs after a jump, coupled with the subsequent improvement in clinical signs, suggests a distinctive feature where there is intermittent misalignment and realignment of the atlantoaxial joint, resulting in intermittent spinal cord compression. The parasagittal approach is a modification of the ventral approach that requires less dissection, reduces tissue recovery time, involves less manipulation, and minimizes the displacement of structures like the trachea. Initially, ventral stabilization with screws and polymethylmethacrylate was performed as per the routine, but the implant failed. Subsequently, a second intervention was conducted, involving the addition of transarticular pins, a screw at C3 and screws with larger diameter in the same holes used previously, resulting in a successful therapeutic outcome. The parasagittal approach offers advantages as an alternative to the conventional ventral approach. Reports of failure of the stabilization method may be useful for surgeons in developing a reintervention strategy. The use of an additional screw, intraarticular pins and larger screws can be considered valid in the case of patients more active Although the presentation of the disease in animals over two years of age is relatively uncommon, it should still be considered as a differential diagnosis when the clinical signs are compatible. Keywords: canino, instabilidade atlantoaxial, neurocirurgia, neurologia, malformações cervicais. Título: Subluxação atlantoaxial em uma cadela adulta - diagnóstico e tratamento por estabilização cirúrgica ventral Descritores: canine, atlantoaxial instability, neurosurgery, neurology, cervical malformations.